2022
DOI: 10.1155/2022/9147416
|View full text |Cite|
|
Sign up to set email alerts
|

Anesthesia Effect of Remifentanil Combined with Propofol in Laparoscopic Cholecystectomy and Its Impact on Postoperative Cognitive Recovery

Abstract: Objective. To investigate the anesthesia effect of remifentanil combined with propofol for laparoscopic cholecystectomy and its impact on postoperative cognitive recovery. Methods. A total of 120 patients who underwent laparoscopic cholecystectomy in our hospital from February 2019 to June 2021 were recruited and assigned into either control group or experimental group at a ratio of 1 : 1 via the random number table method. The patients in the control group were anesthetized with fentanyl combined with propofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%